Enhancing Vocabulary Mastery through Song-Based Learning Among Seventh-Grade students at SMP Negeri 4 Padangsidimpuan - Natasya, Alifia; Maharani; Harahap, Tinur Rahmawati (Yayasan Kajian Riset dan Pengembangan RADISI, 2023)
This study investigates the effectiveness of incorporating songs into vocabulary teaching to enhance vocabulary mastery among seventh-grade students at SMP Negeri 4 Padangsidimpuan. With a backdrop of traditional vocabulary teaching methods yielding limited engagement and retention, this research aimed to explore a more dynamic approach. The Classroom Action Research (CAR) methodology was employed over two cycles, involving pre-tests, interventions using songs, and post-tests to measure outcomes. Initial observations and a pre-test established a baseline, revealing students' vocabulary scores predominantly in the poor category with an average of 43.67. Subsequent interventions involved teaching vocabulary through carefully selected songs, aligning with educational objectives. The results were promising, showing significant improvements in post-test scores across both cycles, with final scores averaging at 82.5, and 88.9% of students meeting the minimal completeness criteria (KKM). This study concludes that song-based learning is an effective strategy for improving vocabulary mastery, making a strong case for its integration into language teaching practices. It suggests that educators consider adopting similar interactive and engaging methods to enhance language acquisition, catering to diverse learning preferences and needs.